2015
DOI: 10.1016/j.chom.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Microbiota-Derived Short-Chain Fatty Acids and Intestinal Epithelial HIF Augments Tissue Barrier Function

Abstract: SUMMARY Interactions between the microbiota and distal gut are fundamental determinants of human health. Such interactions are concentrated at the colonic mucosa and provide energy for the host epithelium through the production of the short-chain fatty acid butyrate. We sought to determine the role of epithelial butyrate metabolism in establishing the austere oxygenation profile of the distal gut. Bacteria-derived butyrate affects epithelial O2 consumption and results in stabilization of hypoxia-inducible fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
983
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,282 publications
(1,024 citation statements)
references
References 43 publications
25
983
0
16
Order By: Relevance
“…Butyrate-derived acetyl-CoA is made available for oxidative phosphorylation and becomes a prominent fuel for colonic epithelial cells (80). It was recently revealed by Kelly et al that butyrate increases epithelial O 2 consumption to the extent that cells sense metabolic hypoxia and HIF is stabilized (81). These same studies revealed that the lack of microbiota (using germ-free or antibiotic-treated mice) resulted in the depletion of butyrate and loss of HIF stabilization.…”
Section: Host-microbial Metabolism and Tissue Barriermentioning
confidence: 99%
“…Butyrate-derived acetyl-CoA is made available for oxidative phosphorylation and becomes a prominent fuel for colonic epithelial cells (80). It was recently revealed by Kelly et al that butyrate increases epithelial O 2 consumption to the extent that cells sense metabolic hypoxia and HIF is stabilized (81). These same studies revealed that the lack of microbiota (using germ-free or antibiotic-treated mice) resulted in the depletion of butyrate and loss of HIF stabilization.…”
Section: Host-microbial Metabolism and Tissue Barriermentioning
confidence: 99%
“…SCFAs decrease intestinal pH, which can alter the gut microbiota by inhibiting the growth of pathogens and reduce the expression of microbial virulence genes (63). Recently, it was shown that epithelial cell lines metabolize the SCFA butyrate (and to a lesser extent propionate and acetate), resulting in oxygen reduction that leads to stabilization of the transcription factor, hypoxia-inducible factor 1a (Hif-1a) (64). In the intestine, this transcription factor has been implicated in gut barrier function by regulating inflammation (65) and apoptosis (66).…”
Section: Impact Of Df On the Gut The Gatekeeper Of The Bodymentioning
confidence: 99%
“…As with other SCFAs, butyrate is consumed by the host as an energy source; however, unlike the other common SCFAs, such as propionate and acetate, butyrate is the preferred energy source for colonocytes (2) and is rapidly absorbed and used by the colonic epithelium. This rapid oxidation of butyrate reduces local oxygen concentrations, causing the epithelia to become hypoxic and thus limiting the growth of facultative aerobic pathogens, such as Salmonella species (3,4). In addition, butyrate alters host gene expression to promote immune tolerance to the colonic microbiota and to improve the barrier function of the colonic epithelium.…”
mentioning
confidence: 99%